Into the waves - Thorpe, Kiki; Christy, Jana; Disney Enterprises (1996- ) (New York : Random House, Disney Enterprises, Inc., 2016)
Lainey gets her first pet, a goldfish, but when he escalpes in Pixie Hollow, the girls embark on a river adventure through Never Land to try and find him.
"A Stepping Stone book."
510
Keywords: Fairies -- Juvenile fiction; Magic -- Juvenile fiction; Friendship -- Juvenile fiction; Goldfish -- Juvenile fiction